Targeting calpain in synaptic plasticity - Baudry, Michel (2013)
INTRODUCTION: Calpains represent a family of neutral, calcium-dependent proteases, which modify the function of their target proteins by partial truncation. These proteases have been implicated in numerous cell functions, including cell division, proliferation, migration, and death. In the CNS, where μ-calpain and m-calpain are the main calpain isoforms, their activation has been linked to synaptic plasticity as well as to neurodegeneration. This review will focus on the role of calpains in synaptic plasticity and discuss the possibility of developing methods to manipulate calpain activity for therapeutic purposes. AREAS COVERED: This review covers the literature showing how calpains are implicated in synaptic plasticity and in a number of conditions associated with learning impairment. The possibility of developing new drugs targeting these enzymes for treating these conditions is discussed. EXPERT OPINION: As evidence accumulates that calpain activation participates in neurodegeneration and cancer, there is interest in developing therapeutic approaches using direct or indirect calpain inhibition. In particular, a peptide derived from the calpain truncation site of mGluR1α was shown to decrease neurodegeneration following neonatal hypoxia/ischemia. More selective approaches need to be developed to target calpain or some of its substrates for therapeutic indications associated with deregulation of synaptic plasticity.